Pengembangan Bahan Ajar Bahasa Inggris Berbasis Esp (English For Nursing) Bagi Mahasiswa Ilmu Keperawatan Pada Perguruan Tinggi Di Provinsi Gorontalo - Puluhulawa, Yulan M.; Mariana, Ana; Mansur, Rona Febriyona (Al-Lisan: Jurnal Bahasa, 2021)
Numerous factors influence students' learning outcomes. Among them is the teaches' use of high-quality instructional materials. Essentially, teachers provide materials to assist students in comprehending the material on a subject to reach the goal properly. When teaching English to nursing students, materials should be based on the students' unique needs, which are addressed in English for Specific Purposes (ESP). This research aimed to describe nursing students' needs for English Instructional Material in University context. This study employed mix method. The data collection techniques used were document, interview, and questionnaire. The document analysis revealed that the learning materials did not meet the needs of nursing students seeking to advance their careers. Additionally, the questionnaire and interview analysis results demonstrate the critical nature of developing English teaching materials for nursing students. As a result, English teaching materials for nursing students are needed to assist them in mastering the English language skills necessary to support their professional careers.t their professional carrier.